Overexpression of AtEDT1/HDG11 in Chinese Kale (Brassica oleracea var. alboglabra) Enhances Drought and Osmotic Stress Tolerance - Zhu, Zhangsheng; Sun, Binmei; Xu, Xiaoxia; Chen, Hao; Zou, Lifang; Chen, Guoju; Cao, Bihao; Chen, Changming; Lei, Jianjun (Frontiers in Plant Science, 2016)
Plants are constantly challenged by environmental stresses, including drought and high salinity. Improvement of drought and osmotic stress tolerance without yield decrease has been a great challenge in crop improvement. The Arabidopsis ENHANCED DROUGHT TOLERANCE1/HOMEODOMAIN GLABROUS11 (AtEDT1/HDG11), a protein of the class IV HD-Zip family, has been demonstrated to significantly improve drought tolerance in Arabidopsis, rice, and pepper. Here, we report that AtEDT1/HDG11 confers drought and osmotic stress tolerance in the Chinese kale. AtEDT1/HDG11-overexpression lines exhibit auxin-overproduction phenotypes, such as long hypocotyls, tall stems, more root hairs, and a larger root system architecture. Compared with the untransformed control, transgenic lines have significantly reduced stomatal density. In the leaves of transgenic Chinese kale plants, proline (Pro) content and reactive oxygen species-scavenging enzyme activity was significantly increased after drought and osmotic stress, particularly compared to wild kale. More importantly, AtEDT1/HDG11-overexpression leads to abscisic acid (ABA) hypersensitivity, resulting in ABA inhibitor germination and induced stomatal closure. Consistent with observed phenotypes, the expression levels of auxin, ABA, and stress-related genes were also altered under both normal and/or stress conditions. Further analysis showed that AtEDT1/HDG11, as a transcription factor, can target the auxin biosynthesis gene YUCC6 and ABA response genes ABI3 and ABI5. Collectively, our results provide a new insight into the role of AtEDT1/HDG11 in enhancing abiotic stress resistance through auxin- and ABA-mediated signaling response in Chinese kale.